English essentials : what every college student needs to know about grammar, punctuation, and usage - Langan, John, 1942-; Johnson, Beth, 1956- (Dubuque, Iowa : McGraw-Hill, 2013)
A guide to mastering practical English skills. It offers guidance through the grammar, punctuation, and usage skills needed for success in college and beyond. It includes sections that provide essential instructions followed by ample activities to encourage learning in the best possible way: by doing
Becoming a better writer -- Writing assignments -- Fifteen basic skills -- Extending the skills -- Proofreading -- Related matters
Includes index
Keywords: English language -- Grammar -- Problems, exercises, etc; English language -- Punctuation -- Problems, exercises, etc; English language -- Usage -- Problems, exercises, etc